Propranolol and propranolol-LA in essential tremor: a double blind comparative study. - Cleeves, L (1988)
In a double blind, comparative study with 15 patients, a long-acting formulation of propranolol taken once daily (at doses of 160, 240 and 320 mg), was shown to be as effective as conventional propranolol (80 mg three times daily) in reducing the amplitude of essential tremor. The specific protocol employed demonstrated problems inherent in chronic pharmacological trials in essential tremor which have implications for future studies.